Meu corpo ainda quente o corpo feminino na obra de Sheyla Smanioto - Maíra Soalheiro Grade (Revista Odisséia, 2023)
The power relations manifest themselves on our social interactions and act upon the bodies of all individuals. The body, for that matter, constitutes a very important element on social construction of male and female identities — for women, it has the power of preventing personal development possibilities, defining their social roles in family and in society. In this scenario, starting from the assumptions of GilbertDurand ́s imaginary theory, the present work intends to explore, on the figurative context of the novel Meu corpo ainda quente (2020), of Sheyla Smanioto, the idea of feminine body colonization and the many violences that result from it. The bookin question, as an expression of historical and social conditions of the time when it was produced, represents, in its own way, women fight for the exercise of a full citizenship, historically built by claiming a voice that for a long time was denied for them.